Evaluation of the Cow’s Milk and Hen’s Egg Ladder in Daily Practice: A Parent Perspective - Bozic, Manuela; Roth, Michèle S.; Martin, Lina; Werder, Andrea; Bellutti Enders, Felicitas (Klinische Pädiatrie, 2025)
Evaluation of the cow’s milk (CM) and hen’s egg (HE) ladder to improve medical care of children with CM and/or HE allergy. Through an anonymous retrospective online questionnaire, we investigated parent perspectives regarding the therapy option of a CM and HE ladder in children with CM and/or HE allergy. Of the 54 families contacted, 29 took part in the study. 19/29 children had already completed the ladders when the survey took place. 19/29 children showed an allergic reaction during the treatment of whom 17 presented skin rashes. 16/29 parents were anxious to rise to the next step in the protocol. 15/29 had difficulties with the implementation of the therapy due to the child refusing the offered food and organizational issues. Medical support as well as the ladder as a therapy option were scored satisfactory. The participating parents were satisfied with the therapy option and medical care. We identified two main areas for improvement: First, the suggested food for every step should be more diverse, according to the families’ culture background and nutritional needs/demands. Second, to reduce anxiety regarding the therapy, parents must be informed that although allergic reactions are common, they remain mild. Furthermore, we will suggest step changes under medical supervision, especially in families with a slow progression of the food ladder. With these improvements, the duration of therapy could be shortened, thus reducing the risk of an allergic reaction, the need for medical care by an allergist and therefore reducing healthcare costs.
Keywords: milk ladder; egg ladder; milk allergy; egg allergy; food hypersensitivity; child